2002
DOI: 10.1073/pnas.182407599
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase contributes to tumorigenesis by a telomere length-independent mechanism

Abstract: Once immortalized, human cells are susceptible to transformation by introduction of an oncogene such as ras. Several lines of evidence now suggest that the maintenance of telomere length is a major determinant of replicative lifespan in human cells and thus of the immortalized state. The majority of human tumor cells acquire immortality through expression of the catalytic subunit of telomerase (hTERT), whereas others activate an alternative mechanism of telomere maintenance (ALT) that does not depend on the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
327
3
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(347 citation statements)
references
References 49 publications
13
327
3
4
Order By: Relevance
“…The prevalence of reactivating telomerase for telomere length maintenance versus homologous recombinationbased telomere maintenance in human tumors suggests that telomerase functions go beyond telomere repair in promoting tumor growth (Blasco, 2002;Chang and DePinho, 2002;Stewart et al, 2002). Forced telomerase expression in ALT models confers growth advantages under all tested conditions, including limited cellular cross-talk, low seeding number and in anchorageindependent growth assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of reactivating telomerase for telomere length maintenance versus homologous recombinationbased telomere maintenance in human tumors suggests that telomerase functions go beyond telomere repair in promoting tumor growth (Blasco, 2002;Chang and DePinho, 2002;Stewart et al, 2002). Forced telomerase expression in ALT models confers growth advantages under all tested conditions, including limited cellular cross-talk, low seeding number and in anchorageindependent growth assays.…”
Section: Discussionmentioning
confidence: 99%
“…Although SV40LT inhibitory activity on the p53 and Rb tumor suppressor pathways are adequately replaced by similar p53 and Rb inhibitory activities, with the expression of human papillomavirus E6 and E7 oncoproteins (Kiyono et al, 1998), telomere maintenance by the ALT mechanism is unable to replace TERT expression and promote robust tumorigenesis in nude mice. This implies that the role of telomerase activity in cancer development goes beyond telomere maintenance (Stewart et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether it was the telomere extension activity of telomerase that compensated for FEN1 depletion at the telomeres as suggested by our earlier work, we utilized a catalytically inactive, dominant-negative allele of hTERT (DNhTERT) (Figure 3a). This allele was chosen because earlier work showed that it had no impact on telomere stability in GM847 cells (Stewart et al, 2002). In contrast to that observed in GM847-hTERT cells, FEN1 depletion in GM847-DN-hTERT cells resulted in increased telomeric fusions (Figures 3b and c).…”
Section: Role Of Fen1 In Alt Tumor Cells a Saharia And Sa Stewartmentioning
confidence: 97%
“…A minimum of 100 cells were counted for each condition and the average for two experiments is presented. Cell culture, western blot analysis, viral constructs and production as well as metaphase preparation and statistical analyses were as described earlier (Stewart et al, 2002(Stewart et al, , 2003Saharia et al, 2008).…”
Section: Flap Endonuclease 1 Depletion In Telomerase-positive Cells Dmentioning
confidence: 99%
“…Telomerase is able to elongate telomeres (Greider & Blackburn, 1985); however, it often has diminished activity in adults, particularly in long‐lived species (Dong, Masutomi, & Hahn, 2005; Haussmann et al., 2007; Hornsby, 2007; Stewart et al., 2002; Tollefsbol & Andrews, 2001). There is some evidence that telomerase may be more active in bone marrow, gonads, and intestine cell lines in adult birds of long‐lived species ( Sterna hirundo; Oceanodroma leucorhoa ) compared to short‐lived ones ( Taeniopygia guttata; Tachycineta bicolor ) (Haussmann et al., 2007).…”
Section: Introductionmentioning
confidence: 99%